TRANSITIVITY SYSTEM AS THE REPRESENTATION OF FIELD IN BARRACK OBAMA'S INAUGURAL SPEECH - Muhammad Saibani Wiyanto (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2017)
Understanding how words and grammatical choices are realized the context of situationis needed to understand a discourse.One of context of situation elements is field (topic which is talked about) that realized through transitivity system.The objective of this study were to describe the three aspects of transitivity system; process, participants and circumstances that associated with the process, and explain the field of Barrack Obama's Inaugural speech based on transitivity system analysis.This studywas qualitative study. Systemic Functional Linguistics was a theory that used to analyze the data. The data was the utterances which contains of words or phrases referring to transitivity system that taken fromthe transcript of Barrack Obama's Inaugural speech on January 20, 2009. The findingsshowed that the processes that found were material process, relational process, mental process, verbal process, behavioral process, and existential process. The participants were mostly we, our nation, us, you, I, all or America. Circumstances that mostly occur in the data were circumstance of location, manner, cause and accompaniment. Then, the field was Barrack Obama addressed all of the peoplewatching or listening his speech in the world, especially American people to do some actions in making America better